Complications Following Stem Cell Therapy in Inflammatory Bowel Disease - Wei, Hongyun; Liu, Xiaowei; Ouyang, Chunhui; Zhang, Jie; Chen, Shuijiao; Lu, Fanggen; Chen, Linlin (Current stem cell research & therapy, 2017)
Pharmacotherapy and surgery constitute the mainstay of treatment for inflammatory bowel disease (IBD). But post-treatment relapsing and recurrence persist as concerns in patients with IBD. Stem cell therapy (SCT) has emerged as a promising treatment strategy in inflammatory bowel disease (IBD), including hematopoietic stem cells (HST), mensenchymal stem cells (MSCs). However, severe complications limit the clinical use of SCT in IBD. Therefore, this review aims to summarize SCT-associated complications, and illustrate possible prevention strategies. We searched Pubmed for studies which reported the use of SCT to treat patients with IBD. Searching terms included 'IBD' or 'Inflammatory bowel disease' or 'CD' or 'Crohn's disease' and 'stem cell therapy' or 'stem cell transplantation'. HSCT can restore the immune tolerance following chemotherapy-induced immune ablation, and MSCs could affect immune cells or secret trophic factors to treat IBD. However, severe complications limit the clinical use of SCT in IBD. Dominant SCT-associated complications include infection, ectopic tissues, and graft-versus-host disease (GVHD), especially for auto-HSCT. As for infection, bacteremia and virus infection were found after SCT treatment, and the use of anti-microbial regimens could reduce incidences of infection. Ectopic tissue formation in the recipient was observed after treatment with HSCT or MSC. Homing and tissue integration might be the possible mechanisms for not forming ectopic tissues. In addition, GVHD was also observed in allogeneic HSCT. Therefore, autologous HSCT and MSCs transplantation were recommended to avoid GVHD. MSCs with their low immunogenicity property eliminate the need for chemotherapy, and are over HSCT in reducing the risk of severe complications. For better application of SCT in IBD, antimicrobial prophylaxis should be used combined with SCT.